THE USE OF MEDIA TEXTS IN ENGLISH LESSONS IN DEVELOPING INTERCULTURAL COMPETENCE OF B1 LEVEL STUDENTS: THE USE OF MEDIA TEXTS IN ENGLISH LESSONS IN DEVELOPING INTERCULTURAL COMPETENCE OF B1 LEVEL STUDENTS - Turdimuratova, Aysanem (Журнал иностранных языков и лингвистики, 2025)
In today’s increasingly globalized world, intercultural competence has become an essential component of language education. It refers to the ability to communicate effectively and appropriately with people from different cultural backgrounds. Conventional language instruction has historically prioritized linguistic competence, often overlooking the cultural elements that are indispensable for effective communication [3; 682]. Consequently, teaching English as a foreign language should not only focus on linguistic proficiency but also on fostering students’ cultural awareness and understanding. In this regard, the use of media texts in English lessons has proven to be a powerful tool, especially for learners at the B1 level [6: 72-82]. Not only do such texts enrich vocabulary and improve comprehension skills, but they also expose students to diverse cultural perspectives. Therefore, this article explores how media texts contribute to the development of intercultural competence in B1-level students during English language instruction